Japan : - Booth, Alan (Passport Books, 1992)
Alan Booth's remarkable guidebook provides a highly opinionated introduction to the country he has lived in for over 20 years. After an extended tour of Tokyo, Nara, and Kyoto, the reader is guided, prefecture by prefecture, to more remote destinations.